Holman's Department Store, Pacific Grove, California - Peter Stackpole:::Creator::::::::::::
Holman's Building, Holman's Department Store on Lighthouse Avenue, where Steinbeck purchased writing supplies. RESTRICTED USE Originals is in the safe. (3 copies)